Promising New Evergreen Magnolias for Florida - Gary W. Knox (EDIS, 2008)
ENH-1088, a 5-page fact sheet by Gary W. Knox, provides information about new evergreen magnolias being evaluated at NFREC Quincy. Includes references and a table comparing characteristics of new, non-native magnolias with native evergreen Magnolia species. Published by the UF Department of Environmental Horticulture, January 2008.